Prevalence of rhinology related consultations in an ear, nose throat clinic in a period of 1 year - Al-Arayedh, Mohamed; Al-Marzooq, Zainab; Alrowaila, Muneera; Al-Reefy, Heba (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Several studies have been conducted to forecast the top emergencies that are frequently seen among patients in an ENT clinic. In the past four years, there has been only one study that calculates the prevalence of a specific rhinology disease (allergic rhinitis) in five Middle Eastern countries. The results of the study have demonstrated that 1808 of 33,486 subjects enrolled in the study have fulfilled the case definition of allergic rhinitis. The mentioned study has only reviewed active cases of allergic rhinitis, disinclining other rhinology conditions that patients frequently complain of. The following paper will calculate the prevalence of common rhinology conditions generally in a specialized ENT clinic in the Kingdom of Bahrain over a period of 1 year. Methods: Patients’ information was collected prospectively on monthly basis starting from June 2021 until June 2022. The patients were registered under a senior ENT consultant at a semi-governmental hospital in The Kingdom of Bahrain. Results: Out of 2711 subjects enrolled in the study, 1424 patients have been registered with rhinology related complaints, exhibiting approximately (52.4%) of the total sample size. Allergic rhinitis was the most prevalent clinically diagnosed rhinology disease and Rhinoplasty surgery was the most frequently operated surgery. The socio-demographics of the study measured (52.0%) Higher females ration between Rhinology patients. In contrast, A higher percentage of males attended the clinic for otology/ear consultations (57.2%). Conclusions: Rhinology related consultations is concluded to be more prevalent compared to otology and laryngology.